2006
DOI: 10.2307/3844674
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Immune-Mediated Apparent Competition in Genetically Diverse Malaria Infections

Abstract: Competitive interactions between coinfecting genotypes of the same pathogen can impose selection on virulence, but the direction of this selection depends on the mechanisms behind the interactions. Here, we investigate how host immune responses contribute to competition between clones in mixed infections of the rodent malaria parasite Plasmodium chabaudi. We studied single and mixed infections of a virulent and an avirulent clone and compared the extent of competition in immunodeficient and immunocompetent mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(81 citation statements)
references
References 6 publications
2
79
0
Order By: Relevance
“…Second, co-infecting strains may compete over some limiting resource. Third, there can be immune-mediated competition, if the immune response is strain-transcending and multiple infections induce a stronger immune response than single infections (for example, because multiple infections have higher infection intensities during the early phase of the infection, before infection intensities are regulated by the immune response) [34,35]. Which of these mechanisms is most important in the case of B. afzelii?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, co-infecting strains may compete over some limiting resource. Third, there can be immune-mediated competition, if the immune response is strain-transcending and multiple infections induce a stronger immune response than single infections (for example, because multiple infections have higher infection intensities during the early phase of the infection, before infection intensities are regulated by the immune response) [34,35]. Which of these mechanisms is most important in the case of B. afzelii?…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to elucidate the relative importance of different types of competition from the current dataset. Instead, infection experiments where different aspects of the host phenotype are modified are required [34,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a rodent malaria model, P. chabaudi in laboratory mice, we and others have experimentally demonstrated that densities of individual clones within an infection are severely suppressed when coinfecting clones are present (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). This competitive suppression substantially reduces the density of transmission stages (42,43), and hence transmission of individual clones to mosquitoes (33,35,36).…”
Section: Aims Of Patient Treatmentmentioning
confidence: 99%
“…Even at the within-host level, within-host microhabitats or tissues may vary with respect to the resources they offer or the risk of mortality to symbionts [11][12][13]. Moreover, each host and each microhabitat offers limited resources which are partitioned among symbionts creating the possibility of strong inter-and intraspecific competition among symbionts sharing a host [14][15][16]. Because hosts are variable in qualities that can directly influence symbiont fitness, it is probable that natural selection favours symbionts that move among hosts discriminately, just as free-living organisms display evolved condition-dependent dispersal strategies [17][18][19].…”
Section: Introductionmentioning
confidence: 99%